NMI promotes cell proliferation through TGFβ/Smad pathway by upregulating STAT1 in colorectal cancer. Issue 1 (23rd June 2019) - Ji, Dongjian; Feng, Yifei; Peng, Wen; Li, Jie; Gu, Qi'ou; Zhang, Zhiyuan; Qian, Wenwei; Wang, Qingyuan; Zhang, Yue; Sun, Yueming
Abstract: Colorectal cancer (CRC) is still a fatal health problem around the world. The underlying mechanisms of CRC have not been fully elucidated. N‐myc interactor (NMI) acts as an oncogene or a tumor‐suppressor gene in several kinds of cancers but CRC. Here, the expression of NMI was found higher in CRC tissues and cells. Higher expression of NMI indicated the poorer prognosis of CRC patients. Moreover, the proliferation of CRC cells was suppressed significantly after we silenced the expression of NMI, while overexpression of NMI promoted CRC cell proliferation. Flow cytometry demonstrated that NMI promoted cell proliferation through facilitating cell transition from the G1 phase to the S phase. Furthermore, it was found that NMI suppressed the phosphorylation of Smad3 by upregulating the expression of STAT1. The effect of NMI depletion on cell proliferation could be reversed by using Smad3 inhibitor SIS3. In summary, our findings demonstrated that NMI promoted cell proliferation via TGFβ/Smad pathway and could indicate the prognosis of patients with CRC. Abstract : N‐myc interactor (NMI) was found upregulated in colorectal cancer (CRC) and higher expression of NMI indicated the poorer prognosis of CRC patients. It was also found that NMI could promote CRC cell proliferation through inhibiting TGFβ/Smad signaling pathway via upregulating STAT1.